2005
DOI: 10.1631/jzus.2005.b0457
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenicity of bacterium, Xenorhabdus nematophila isolated from entomopathogenic nematode (Steinernema carpocapsae) and its secretion against Galleria mellonella larvae

Abstract: Abstract:The entomopathogenic bacterium, Xenorhabdus nematophila was isolated from the hemolymph of Galleria mellonella infected with Steinernema carpocapsae. The bacterial cells and its metabolic secretions have been found lethal to the Galleria larvae. Toxic secretion in broth caused 95% mortality within 4 d of application whereas the bacterial cells caused 93% mortality after 6 d. When filter and sand substrates were compared, the later one was observed as appropriate. Similarly, bacterial cells and secreti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 10 publications
1
12
0
Order By: Relevance
“…This may suggest that metabolites with insecticidal properties that were produced by X. stokiae isolate PB09 are more likely to be secreted to culture supernatant. Mahar et al (2005) also found that X. nematophila cell-free metabolites required 4 d to kill 95% G. mellonella larvae whereas cell suspension needed up to 6 d to induce 93% mortality. There are several reports indicated that Xenorhabdus sp.…”
Section: Discussionmentioning
confidence: 92%
“…This may suggest that metabolites with insecticidal properties that were produced by X. stokiae isolate PB09 are more likely to be secreted to culture supernatant. Mahar et al (2005) also found that X. nematophila cell-free metabolites required 4 d to kill 95% G. mellonella larvae whereas cell suspension needed up to 6 d to induce 93% mortality. There are several reports indicated that Xenorhabdus sp.…”
Section: Discussionmentioning
confidence: 92%
“…Both are nematode associated insect pathogens and are released by the vector after entering the haemocoele of insect larvae [70]. Death by toxic substrates and tissue disintegration through the bacteria occurs within 48 h. An nematode unrelated, but also larval specific insect pathogen is Pseudomonas entomophila dissolving the tissues and killing larvae with insecticidal toxins in similar time spans [49].…”
Section: Resultsmentioning
confidence: 99%
“…This was similar to the previous report of Bussaman et al (2012) which showed that cell-free supernatant of X. stokiae culture led to both the highest miticidal activity (89.00 %) and the lowest mite fecundity (41.33 eggs/ gravid female), when compared to its whole cell suspension and crude cell extract. The cell-free supernatant of X. nematophila was also found to be highly virulent to the insect pests, including S. exgua, P. xylostella, O. sulcatus, and S. gregaria, within 48 h (Mahar et al 2008), and also be extremely toxic to G. mellonella (95 % mortality) when being applied at the concentration of 4 × 10 7 cells/ ml (Mahar et al 2005). This may suggest that cell-free supernatant of Xenorhabdus spp.…”
Section: Effects Of X Stockiae Pb09 Bioformulations On Miticidal Actmentioning
confidence: 99%
“…Cell suspensions and cell-free supernatants of Xenorhabdus spp. have been shown to be highly effective under laboratory conditions for controlling of several insect pests, such as Plutella xylostella L. (Abdel-Razek 2003;Mahar et al 2008), Hopila philanthus (Fuessly) (Ansari et al 2003), Frankliniella occidentalis (Pergande), Thrips tabaci (Lindeman) (Gerritsen et al 2005), Galleria mellonella L. (Mahar et al 2005), Spodoptera exgua (Hubner), Otiorhynchus sulcatus (Fabricius), Schistocerca gregaria (Forskal) (Mahar et al 2008), and Tribolium castaneum (Herbst) (Shresth and Kim 2010). Moreover, Bussaman et al (2009) reported that application with Xenorhabdus nematophila and Photorhabdus luminescens caused the highest mortality of Luciaphorus perniciosus Rack, a mushroom mite, at 85 and 83 %, respectively.…”
Section: Introductionmentioning
confidence: 99%